Study of the thermochromic phase transition in CuMo1−xWxO4 solid solutions at the W L3-edge by resonant X-ray emission spectroscopy - Pudza, Inga; Kalinko, Aleksandr; Cintins, Arturs; Kuzmin, Alexei (Elsevier Ltd., 2021)
Polycrystalline CuMo1−xWxO4 solid solutions were studied by resonant X-ray emission spectroscopy (RXES) at the W L3-edge to follow a variation of the tungsten local atomic and electronic structures across thermochromic phase transition as a function of sample composition and temperature. The experimental results were interpreted using ab initio calculations. The crystal-ﬁeld splitting parameter Δ for the 5d(W)-states was obtained from the analysis of the RXES plane and was used to evaluate the coordination of tungsten atoms. Temperature-dependent RXES measurements were successfully employed to determine the hysteretic behaviour of the structural phase transition between the α and γ phases in CuMo1−xWxO4 solid solutions on cooling and heating, even at low (x < 0.10) tungsten content. It was found that tungsten ions have octahedral coordination for x > 0.15 in the whole studied temperature range (90-420 K), whereas their coordination changes from tetrahedral to octahedral upon cooling for smaller (x ≤ 0.15) tungsten content. Nevertheless, some amount of tungsten ions was found to co-exists in the octahedral environment at room temperature for x < 0.15. The obtained results correlate well with the color change in these solid solutions.
This is the peer reviewed version of the following article: I. Pudza, A. Kalinko, A. Cintins, A. Kuzmin, Acta Mater. 205 (2021) 116581, which has been published in final form at https://www.sciencedirect.com/science/article/abs/pii/S1359645420310181 This article may be used for non-commercial purposes in accordance with Elsevier Terrms and Conditions for Self-Archiving.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; CuMo1−xWxO4; crystal-ﬁeld splitting; resonant X-ray emission spectroscopy (RXES); high-energy resolution ﬂuorescence detected X-ray absorption near-edge structure (HERFD-XANES)